A Survey on the objective of the firm and models of producer behavior in the Islamic framework - Abdullah Yusof, Selamah; Mohd Amin, Ruzita (King Abdul Aziz University, 2007)
This paper presents a review of related works that have been written over the years on the objective of the firm from the Islamic perspective. For the purpose of analysis, a general framework on proper economic conduct and objective of economic order as discussed by al-Ghazali and Maududi, respectively is provided. Several studies that provide mathematical models to explain the producer behavior are further examined in a separate section. Our analysis finds that, in general, the arguments provided in justifying the objective of the firm as found in the various studies have the Islamic framework in mind. The theoretical models that have been developed can be used as a basis to formulate a more comprehensive model on Islamic producer behavior that provides more rigor and robustness to the analysis.